Distribution and biology of the Blackmouth catshark Galeus melastomus in the Strait of Sicily (Central Mediterranean Sea) - RAGONESE, S.; NARDONE, G.; OTTONELLO, D.; GANCITANO, S.; GIUSTO, G.B.; SINACORI, G. (Mediterranean Marine Science, 2009)
The Blackmouth catshark, Galeus melastomus, Rafinesque, 1810 (Carcharhiniformes; Scyliorhinidae), is a common, although at present discarded, by- catch of the bottom trawl fisheries in the Strait of Sicily. Given its ecological interest, data gathered in experimental bottom trawl surveys were analysed in order to describe its distribution and main biological traits. The Blackmouth catshark was sampled almost exclusively on the upper slope (200-800), showing the highest frequency of occurrence (69-100%), biomass (BI; 10-85 kg*km-2) and density (DI; 54-506 N*km-2) indexes in the deeper (501-800m) grounds. Individual size (total length, TL, mm) were between 70-590 and 90-510 in females and males, respectively. The sex ratio (SR) was around 0.5. The SR by size showed a gradual decrease till 450 mm class size, followed by an increase up 1 after 500 mm. Virginal/immature specimens represented the bulk of the samples in both females (77%) and males (65%); the length at 50% of sexual maturity (Lm50%) and corresponding maturity range (Lm25% - Lm75% ) was 433 (423-443) and 380 (366-394) mm, respectively.